Pemberian Informasi Mengenai Pencegahan Penularan Corona Virus Disease 2019 Kepada Masyarakat Mesjid Al-Irwan Kelurahan Batunadua Jae Kota Padangsidimpuan Tahun 2020 - Delfi Ramadhini; Novita Sari Batubara; Dewani Harahap (Universitas Aufa Royhan Di Kota Padangsidipuan, 2020)
The novel coronavirus (2019-nCoV) is a new type of virus that has never been previously identified in humans. The World Health Organization (WHO) announced the name of the new virus Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) and the name of the disease as Coronavirus Disease (COVID-19) which is caused by a virus. WHO declared COVID-19 a pandemic. In the world, the number of Covid-19 cases has 634,835 cases and 33,106 deaths. In Indonesia, the Covid-19 death rate has reached 3,087 or 2.3% with a cure rate of 45,726 people. The purpose of this PKM is to motivate the congregation and the community around the mosque about the importance of preventing the transmission of covid-19. PKM activities are carried out with the health education method using posters and leaflets to the community of the Al-Irwan Mosque, Batunadua Jae Village, Padangsidimpuan City, totaling 45 people. The results of this counseling activity were continued by providing an evaluation to the Al-Irwan Mosque Community, Batunadua Jae Village, Padangsidimpuan City, namely questions and answers about the material given. There were two questions that were given by the extension agent to the people of Masjid Al-Irwan, Batunadua Jae Village, Padangsidimpuan City. Based on the answers given, it shows that the people of Masjid Al-Irwan, Batunadua Jae Village, Padangsidimpuan City understand the material provided by the instructor. PKM activities carried out went well. The people of Al-Irwan Mosque, Batunadua Jae Village, Padangsidimpuan City who participated in the activity seemed enthusiastic in participating in the counseling activities.